Mathematical And Statistical Analysis Of Pedagogical Experimental Work Of Preschool Children Of Middle Age (Journal of Pedagogical Inventions and Practices, 2025)
This article presents a mathematical and statistical analysis of the pedagogical experimental work of middle-aged preschoolers. According to the results of studies conducted by many scientists, children show that the dynamics of physical development and physical fitness of a schoolchild depends on the nature of consistently performed physical exercises. For the development of physical qualities of preschoolers, the most important issue is the correct organization and implementation of activities based on active games and exercises with elements of game sports. Based on them, we tried to highlight the results of physical fitness of middle-aged children before the experiment.